Direct targeting of HSP90 with daurisoline destabilizes β-catenin to suppress lung cancer tumorigenesis. (1st October 2020) - Huang, Xiao-Hui; Yan, Xin; Zhang, Qi-Hua; Hong, Pan; Zhang, Wei-Xia; Liu, Ya-Ping; Xu, Wen Wen; Li, Bin; He, Qing-Yu
Abstract: Lung cancer is the most frequent cancer worldwide with a poor prognosis. Identification of novel cancer targets and useful therapeutic strategies without toxicity are urgently needed. In this study, we screened natural products for anticancer bioactivity in a library consisting of 429 small molecules. We demonstrated for the first time that daurisoline, a constituent of Rhizoma Menispermi, repressed lung cancer cell proliferation by inducing cell cycle arrest at the G1 phase. Furthermore, daurisoline was found not only to suppress the growth of lung tumor xenografts in animals without obvious side effects, but also to inhibit cell migration and invasion. Mechanistically, quantitative proteomics and bioinformatics analyses, Western blotting and qRT-PCR confirmed that daurisoline exerted its anticancer effects by inhibiting the expression levels of β-catenin and its downstream targets c-myc and cyclin D1. Furthermore, our data from Drug Affinity Responsive Target Stability (DARTS), isothermal titration calorimetry (ITC) and a series of functional assays demonstrated that daurisoline could target HSP90 directly and disrupt its interaction with β-catenin, therefore increasing the ubiquitin-mediated proteasomal degradation of β-catenin. This study reveals that daurisoline could be a promising therapeutic strategy for the treatment of lung cancer. Highlights: Functional screening identifies daurisoline as a novel anticancer agent in vitro and in vivo . . Daurisoline suppresses lung tumorigenesis by inducing cell cycle arrest. . Daurisoline destabilizes β-catenin to inhibit c-Myc and cyclin D1 expression by directly targeting HSP90.